The Effect of Sintering Time on The Formation of The BPSCCO-2212 Superconductor Phase at The Levels of Ca = 1.10 Using The Wet Mixing Method - Retno Asih; Suprihatin Suprihatin; Simon Sembiring (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
This research was conducted to determine the effect of sintering time on to phase formation of superconducting BPSCCO-2212 with Ca content 1.10 by calculating the level of purity of the phases formed and looking at the microstructure. The variation of sintering time was 10, 20, 30, and 40 hours using the wet mixing method. The sample was calcinated at 800 °C for 10 hours and sintered at 830 °C. The XRD's characterization result showed that the highest volume fraction obtained in BPSCCO-2212/40 hours was 86.72%, while the lowest volume fraction of BPSCCO-2212/30 hours was 53.07%. The relatively high orientation degree of BPSCCO-2212/30 hours was 13.59%, while the lowest orientation degree of BPSCCO-2212/20 hours was 7.67%. The SEM's characterization result shows that all samples have not been oriented, and many voids (space between the plates) are still generated.